Reconstruction of Legal Protection for Trademarks and Geographical Indications (GI) for Tenun Sulaa Products - Revalina Nur Aliyah Priadi; Edy Nurcahyo; Eko Satria (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze and reconstruct legal protection for trademarks and geographical indications (GI) in Tenun Sulaa products as part of intellectual property that possesses economic and cultural value. The research method employed is normative legal research using statutory and conceptual approaches. The findings indicate that, normatively, Law Number 20 of 2016 on Trademarks and Geographical Indications has provided a comprehensive legal basis for the protection of trademarks and geographical indications as instruments of legal branding for local products. However, its implementation still faces several obstacles, including low public legal awareness, the suboptimal process of geographical indication registration, and limited institutional capacity in managing and protecting GI-based products. Therefore, reconstruction of legal protection is required through strengthening the geographical indication registration system, increasing local community participation as collective rights holders, and integrating trademark and geographical indication protection within regional product branding strategies to enhance local identity, improve regional economic competitiveness, and preserve traditional cultural heritage.